2015
DOI: 10.1002/smll.201500529
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐Inspired Chemical Fabrication of Stretchable Transparent Electrodes

Abstract: Stretchable and transparent electrodes are fabricated by chemical deposition of metal thin films on natural veins of leaves at ambient conditions. These vein-based transparent electrodes show excellent electro-optical property (0.9 Ω sq(-1) at 83% T) even at 50% tensile strains, ideal for flexible and stretchable optoelectronic devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 43 publications
1
70
1
Order By: Relevance
“…More recently, several advances in polymer‐assisted ELD16, 17, 18 have been accomplished for the fabrication of highly conductive metal structures for flexible and stretchable interconnects,19, 20, 21, 22 supercapacitors,23, 24 conductive textiles,25, 26 and optoelectronic devices 27, 28. The polymer‐assisted ELD typically involves three major steps: surface modification of functional polymer anchoring layers, loading of catalyst moieties to the polymer anchoring layer by ion exchange, and site‐selective metal electroless deposition.…”
mentioning
confidence: 99%
“…More recently, several advances in polymer‐assisted ELD16, 17, 18 have been accomplished for the fabrication of highly conductive metal structures for flexible and stretchable interconnects,19, 20, 21, 22 supercapacitors,23, 24 conductive textiles,25, 26 and optoelectronic devices 27, 28. The polymer‐assisted ELD typically involves three major steps: surface modification of functional polymer anchoring layers, loading of catalyst moieties to the polymer anchoring layer by ion exchange, and site‐selective metal electroless deposition.…”
mentioning
confidence: 99%
“…Conventionally, indium tin oxide (ITO) film is a ubiquitous transparent electrode of optoelectronics due to excellent sheet resistance and transparency (10 Ω sq −1 at 90% transmittance), but its brittleness by ceramic nature limits its further application to deformable devices. [53,54] Therefore, potential alternative materials have been extensively studied for ST electrodes, including CNTs, [55][56][57][58][59][60][61][62][63] graphene, [64][65][66][67][68][69] metallic NWs, [16,36,47, metallic grid/nanostructure, [94][95][96][97][98][99][100] conducting polymers, [52,[101][102][103][104][105][106][107] and hybrid composites. [39,[108][109][110][111][112][113][114] The performances of STECs are summarized in Table 1.…”
Section: Stecsmentioning
confidence: 99%
“…[96] The zig-zag shaped Ag NP-based electrode retained its original conductivity up to 50% strain. Yu et al used veins in leaves as a template to create Cu based-electrodes by the chemical deposition method, [97] which retained their original electrical property up to 50% strain.…”
Section: Metal Nanoarchitecture-based Stecmentioning
confidence: 99%
“…SEM images showed that the cotton-AgNWs composite exhibited an interconnected, porous 3D framework of randomly oriented, crinkly sheets with continuous macropores, similar to those of previous conductive networks. [25][26][27] The change of porosity of cotton before and aer dip-coating was unobvious. As shown in Fig.…”
Section: Fabrication Of Stretchable Conductormentioning
confidence: 99%